The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.2306/scienceasia1513-1874.2015.41.392
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory activity of a Vernonia cinerea methanolic extract in vitro

Abstract: Vernonia cinerea Less. (Asteraceae) is a herbaceous plant commonly found in SE Asia. Different parts of V. cinerea have been used in various folklore medicine applications, including reducing inflammation and detoxification. This study investigates the effects of V. cinerea methanolic extract on the mouse immune system in vitro. Cytokine detection of ConA-stimulated splenocytes using ELISA, mitogen-induced splenocyte proliferation, and phagocytic activity were assayed. The results show that the extract shifted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…is a plant in Family Asteraceae. It has several activities such as antioxidant activity [15], anti-inflammatory activity [6, 7], and radioprotective activity [8]. Furthermore, it also has antitumor activity, antimicrobial activity, antidiabetic activity, etc.…”
Section: Introductionmentioning
confidence: 99%
“…is a plant in Family Asteraceae. It has several activities such as antioxidant activity [15], anti-inflammatory activity [6, 7], and radioprotective activity [8]. Furthermore, it also has antitumor activity, antimicrobial activity, antidiabetic activity, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Both plants had strong anti-inflammatory properties. A previous study reported that CC extract significantly inhibited the secretion of IFN-γ in a dose-dependent fashion, while IL-10 anti-inflammatory cytokine increased [ 48 ]. Identified isothiocyanates from MO leaf extract significantly decreased gene expression and production of inflammatory mediators in RAW macrophages [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…These cytokines contribute to the pathogenesis and maintenance of the usual neuropathy presented in diabetic patients, promoting nervous excitability and therefore, inducing pain. [91][92][93] As for the antimicrobial activity of eugenol, there is a general idea about its action mechanism, which relates to the alteration of its permeability mechanism by damaging and altering lysosome, microsome, and cell walls. This damage causes bacterial death by the leakage of its essential cell constituents.…”
Section: Eugenolmentioning
confidence: 99%